PENANGGULANGAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN - Anwar, Mohammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Problem solving must be done in a good way and not excessive, there is no physical beating, no shouting and or cursing that causes physical or mental pressure on the opponent. Domestic violence can be said if the behavior seems to attack, coerce and threaten even physical violence. Domestic violence must be avoided and perpetrators of domestic violence are included in criminal offenses. Domestic violence is any action or action taken against an opponent, both wife and husband, that results in misery and even physical, sexual and psychological disabilities, all of which result in the deprivation of one's independence and freedom in the household. Stages of the methodology in this study is the type of research using normative juridical. The results of the study said that the factors behind the existence of domestic violence were caused by misunderstandings, poor communication, loss of harmony in the household, mistakes made by both wife and husband, economic problems, environment, alcohol and marriage. force.